Abu bakr siddiq: the first caliph of islam - Khan, Nafisa; Gurmeet (Goodword Books Delhi-NCR, India, 2022)
"The Story of Abu Bakr Siddiq: The First Caliph of Islam" by Nafisa Khan recounts the life, leadership, and contributions of Abu Bakr, the close companion of Prophet Muhammad and the first caliph of Islam.